Effects on alcohol consumption of announcing and implementing revised UK low-risk drinking guidelines: findings from an interrupted time series analysis. Issue 11 (19th July 2020) - Holmes, John; Beard, Emma; Brown, Jamie; Brennan, Alan; Meier, Petra S; Michie, Susan; Stevely, Abigail K; Webster, Laura; Buykx, Penny F
Abstract : Background: In January 2016, the UK announced and began implementing revised guidelines for low-risk drinking of 14 units (112 g) per week for men and women. This was a reduction from the previous guidelines for men of 3–4 units (24–32 g) per day. There was no large-scale promotion of the revised guidelines beyond the initial media announcement. This paper evaluates the effect of announcing the revised guidelines on alcohol consumption among adults in England. Methods: Data come from a monthly repeat cross-sectional survey of approximately 1700 adults living in private households in England collected between March 2014 and October 2017. The primary outcomes are change in level and time trend of participants' Alcohol Use Disorders Identification Test—Consumption (AUDIT-C) scores. Results: In December 2015, the modelled average AUDIT-C score was 2.719 out of 12 and was decreasing by 0.003 each month. After January 2016, AUDIT-C scores increased immediately but non-significantly to 2.720 (β=0.001, CI −0.079 to 0.099) and the trend changed significantly such that scores subsequently increased by 0.005 each month (β=0.008, CI 0.001 to 0.015), equivalent to 0.5% of the population increasing their AUDIT-C score by 1 point each month. Secondary analyses indicated the change in trend began 7 months before the guideline announcement and that AUDIT-C scores reduced significantly but temporarily for 4 months after the announcement (β=−0.087, CI −0.167 to 0.007). Conclusions: Announcing new UK drinking guidelines did not lead to a substantial or sustained reduction in drinking or a downturn in the long-term trend in alcohol consumption, but there was evidence of a temporary reduction in consumption.